Immobilized lipase-catalysed synthesis of fructose oleate ester in ionic liquid [Bmim][TfO] and tert-butanol solvent systems - Abdul Rahman, Mohd Basyaruddin; Chumati, Mohd Rizal; Hamidon, Noor Fazrieyana; Asmawi, Azren Aida; Mohammad Latif, Muhammad Alif; Abdulmalek, Emilia (Malaysian Institute of Chemistry, 2023)
Fructose oleate is one of the most sought-after sugar esters, but its production is challenging due to the poor solubility of its substrates. However, 1-butyl-3-methylimidazolium (Bmim)-based ionic liquids can solubilize a wide range of substrates and prevent denaturation of enzymes as their physical and chemical properties can be easily tailored. In this work, the enzymatic synthesis of fructose esters using immobilized lipase was investigated using a series of Bmim-based ionic liquids and tert-butanol as solvents. The reaction conditions were optimized for different esterification parameters, such as fatty acid chain length, enzyme loading, reaction temperature and time. The immobilized lipase was found to be more stable in BmimTfO and had a high affinity towards the monounsaturated acyl donor, oleic acid. Optimum ester conversion (73%) was achieved under ideal reaction conditions comprising low enzyme loading (5% w/w) and a reaction temperature of 60 °C for 72 hours. The synthesis of fructose oleate in BmimTfO under these optimized conditions has great potential for use in many applications.